Isolation and characterization of dematiaceous endophytic fungi isolated from barley (Hordeum vulgare L.) roots and their potential use as phosphate solubilizers - Echeverria, Mariela (2024)
Phosphorus is an element with limited availability in the soil. For this reason, to supply phosphorus to crops, farmers depend on chemical fertilization, which affects the production costs and the environmental quality of the soil and water. However, this situation can be mitigated by using phosphorus-solubilizing fungi. Therefore, the objectives of this work were to identify seven dematiaceous endophytic fungi (Dark Septate Endophytes (DSE) and non-DSE), isolated from roots of a commercial barley crop, and to evaluate their characteristics and behavior in vitro regarding parameters that allow their description and potential use to make fertilizer use more efficient and thus reduce the amount of fertilizer required. The growth rate of each strain at different temperatures and pH values, and their ability to solubilize iron (FePO4), aluminum (AlPO4) and calcium (Ca3(PO4)2) phosphates were evaluated. The fungal isolates belonged to four orders: Pleosporales, Xylariales, Hypocreales and Chaetothyriales. The strains had their highest growth rate between 16°C and 30°C, and a great diversity of responses to the different pH values evaluated. Furthermore, all strains showed ability to solubilize Ca3(PO4)2, two to solubilize AlPO4, and one to solubilize FePO4. The diversity observed among the fungal isolates in terms of their response to pH, temperature, and media containing different insoluble phosphates suggests their adaptability to a wide range of environments, and makes them suitable for further studies aimed to determine their potentiality as biofertilizers.